Factors Affecting Perceptions of Procedural Fairness of Downsizing: A Policy Capturing Approach. (30th April 2015) - Bragger, Jennifer; Evans, Diana; Kutcher, Gene; Sumner, Ken; Fritzky, Emily
<x xml:space="preserve">Abstract</x> Subjects read 67 scenarios about downsizing events in which process improvements suggested by HRD researchers were manipulated, and then rated the degree to which the organization was acting in a fair manner. Factors or cues manipulated in scenarios based on HRD practices and literature included (a) whether the victims were given notice and explanation of the layoffs by management, (b) whether the company provided career training and outplacement assistance to victims, (c) whether the layoff decisions were performance‐based or based on earnings, (d) whether the company was currently nonprofitable or downsizing because of decrease in profitability, (e) whether the company implemented other HRD strategies before considering downsizing, and (f) the size of the organization. Regression analyses found that a majority of subjects based fairness on (a) whether the downsizing decision was performance‐based, (b) whether notice and explanation was given by management, and (c) whether the organization provided career counseling and outplacement assistance. Further, cluster analysis revealed three groups of subjects who utilized cues similarly. Between‐group analyses found that levels of cognitive moral reasoning were related to the amount of variance explained by the cues overall and to the beta weights for several cues. Implications for the field of HRD are discussed.